Role of Cloud Computing Services in Higher Education - Aslamzai, Sebghatullah; Sadat, Sayed Abid (Journal of Natural Sciences – Kabul University, 2025)
This study examines the essential role of cloud services in the higher education system. Education plays a crucial role in maintaining and fostering the economic growth of a country. Today, teaching methods in classrooms are evolving, with most students showing a keen interest in using information technology to access courses and materials. Therefore, it is important to consider the latest technology, cloud services, in teaching and learning. Cloud computing is one of the newest technologies and is currently the most common technology in higher education institutions. Most developed countries have adopted this technology in the higher education sector, as cloud services can help professors and students connect efficiently and share necessary teaching and learning materials. One of the newest technologies today is cloud services, which is currently the most common technology in higher education institutions, most developed countries use this technology in the field of higher education, cloud services can help professors and students connect in a simple and advanced way and share the necessary teaching and learning materials.